The Effect of Non-Performing Loans (NPL) and Operational Expenditure on Operational Income (BOPO) on Return on Assets (ROA) - Hernawati, Euis; Warsiati, Wiwi; Pramanik, Nuniek Dewi (Dinasti Publisher, 2024)
This study aims to determine the effect of Non-Performing Loans (NPL) and Operational Expenditure on Operational Income (BOPO) on Return on Assets (ROA) at Bank Mandiri. The population in this study consists of the financial reports of Bank Mandiri listed on the Indonesia Stock Exchange (IDX) for the period 2016-2023. This research employs a quantitative approach, and the research design utilizes multiple linear regression analysis. The results indicate that the NPL and BOPO variables simultaneously affect ROA. Based on the t-test results, it can be concluded that the NPL variable does not have a significant partial effect on ROA, while the BOPO variable has a significant effect on ROA.